The right to have rights - DeGooyer, Stephanie (Politics, 2018)
"Five leading thinkers on the concept of 'rights' in an era of rightlessness Sixty years ago, the political theorist Hannah Arendt, deprived of her German citizenship as a Jew and in exile from her country, observed that before people can enjoy any of the 'inalienable' Rights of Man--before there can be any specific rights to education, work, voting, and so on--there must first be such a thing as 'the right to have rights.' The concept received little attention at the time, but in our age of refugee crises and extra-state war, the phrase has become the center of a crucial and lively debate. Here five leading thinkers from varied disciplines, including history, law, and politics, discuss the critical issue of the basis of rights and the meaning of radical democratic politics today"--